1977
DOI: 10.1038/bjc.1977.93
|View full text |Cite
|
Sign up to set email alerts
|

A test for mutation theory of cancer: Carcinogenesis by misrepair of DNA damaged by 4-nitroquinoline 1-oxide

Abstract: Summary.-Evidence for a mutation theory of cancer is presented by reviewing the experimental work on 4-nitroquinoline 1-oxide (4NQO) carcinogenesis. 4NQO almost completely mimics u.v. light and produces 4NQO-purine adducts on DNA. When 4NQO-treated cells are held in liquid medium under appropriate conditions, the 4NQO adducts disappear from DNA, in parallel to decrease of premutational damage in Escherichia coli, or pretransformational damage in cultured mouse cells. Post-treatment with caffeine greatly dimini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

1980
1980
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 28 publications
0
19
0
2
Order By: Relevance
“…These results suggest that the mutagenic potential of CP is not strong, at least for genes on the X-chromosome like Piga or Hprt, and that a spontaneous Pig-a mutant frequency as low and as stable as practical may be necessary for detecting any mutagenicity induced by CP. 4-NQO forms stable quinoline monoadducts with purine bases through the enzymatic reduction of its nitro group (Kondo, 1977). A previous report described timeand dose-dependent increases of Pig-a mutant RBCs in rats treated with 4-NQO (Stankowski et al, 2011).…”
Section: Discussionmentioning
confidence: 97%
“…These results suggest that the mutagenic potential of CP is not strong, at least for genes on the X-chromosome like Piga or Hprt, and that a spontaneous Pig-a mutant frequency as low and as stable as practical may be necessary for detecting any mutagenicity induced by CP. 4-NQO forms stable quinoline monoadducts with purine bases through the enzymatic reduction of its nitro group (Kondo, 1977). A previous report described timeand dose-dependent increases of Pig-a mutant RBCs in rats treated with 4-NQO (Stankowski et al, 2011).…”
Section: Discussionmentioning
confidence: 97%
“…4NQO is an electrophile and a powerful carcinogen and mutagen (18). It is a UV-mimetic agent and forms charge-transfer complexes with 5Ј-deoxyribonucleotides (19,20). 4NQO forms DNA adducts and causes a wide range of DNA lesions including single-strand breaks, pyrimidine-dimer formation, abasic sites, and oxidized bases.…”
mentioning
confidence: 99%
“…The modified base can also pair with thymine, and not only with cytosine . UV light (Kapetanaki et al, 2006), ionizing radiation and various chemicals (Kondo, 1977;Shrivastav et al, 2010) are examples of exogenous genotoxic agents. Some of them, such as UV light, ionizing radiation and tobacco-derived chemicals, have been firmly established, by epidemiologic, animal and in vitro studies, as carcinogens.…”
Section: Dna Lesions: Types Origins and Consequencesmentioning
confidence: 99%
“…For instance, defects in various DNA repair pathways in hereditary diseases have been linked to the predisposition to a number of cancers (Heinen et al, 2002) (section 5). The importance of DNA repair dynamics in cancer biology became evident as early as the 1970s, when it was observed that mice treated with 4-nitroquinoline 1-oxide (4NQO), a chemical mutagen, displayed increased mortality and reduced incidence of tumors if treated with caffeine, up to five days after treatment with 4NQO (Kondo, 1977). Caffeine is now known to inhibit ATM and ATR kinases and, hence, DDR (Sarkaria et al, 1999).…”
Section: Dna Repair and Misrepair In Cancer: When The Remedy Is Worsementioning
confidence: 99%